Horizontal and vertical food web structure drives trace element trophic transfer in Terra Nova Bay, Antarctica. (March 2019) - Signa, Geraldina; Calizza, Edoardo; Costantini, Maria Letizia; Tramati, Cecilia; Sporta Caputi, Simona; Mazzola, Antonio; Rossi, Loreto; Vizzini, Salvatrice
Abstract: Despite a vast amount of literature has focused on trace element (TE) contamination in Antarctica during the last decades, the assessment of the main pathways driving TE transfer to the biota is still an overlooked issue. This limits the ability to predict how variations in sea-ice dynamics and productivity due to climate change will affect TE allocation in the food web. Here, food web structure of Tethys Bay (Terra Nova Bay, Ross Sea, Antarctica) was first characterised by analysing carbon and nitrogen stable isotopes (δ 13 C, δ 15 N) in organic matter sources (sediment and planktonic, benthic and sympagic primary producers) and consumers (zooplankton, benthic invertebrates, fish and birds). Diet and trophic position were also characterised using Bayesian mixing models. Then, relationships between stable isotopes, diet and TEs (Cd, Cr, Co, Cu, Hg, Ni, Pb and V) were assessed in order to evaluate if and how horizontal (organic matter pathways) and vertical (trophic position) food web features influence TE transfer to the biota. Regressions between log[TE] and δ 13 C revealed that the sympagic pathway drives accumulation of V in primary consumers and Cd and Hg in secondary consumers, and that a coupled benthic/pelagic pathway drives Pb transfer to all consumers. Regressions between log[TE] and δ 15 N showed that only Hg biomagnifies across trophic levels, while all the others TEs showed a biodilution pattern, consistent with patterns observed in temperate food webs. Although the Cd behavior needs further investigations, the present findings provide new insights about the role of basal sources in the transfer of TEs in polar systems. This is especially important nowadays in light of the forecasted trophic changes potentially resulting from climate change-induced modification of sea-ice dynamics. Graphical abstract: Image 1 Highlights: Horizontal and vertical food web structure was characterised using δ 13 C and δ 15 N. Trace element (TE) transfer was assessed in the Antarctic food web. Sympagic and pelagic pathways drove Cd and Hg transfer to invertebrates. Benthic pathway (sediment and phytodetritus) drove Pb to invertebrates. Hg concentration increased along trophic levels and biomagnified. Abstract : Depiction of trace element transfer in the Antarctic food web highlighted an important role of both sympagic and pelagic pathways, suggesting that forecasted modification of sea-ice dynamics due to climate change may alter contaminant accumulation and biomagnification patterns.